Alley cropping vegetable crops with leucaena in southern Nigeria - Chen, S.Y.; Kang, B.; Caveness, F.E. (1989)
Abstract. An alley cropping trial with various vegetable crops and Leucaena leucocephala (Lam.) de W it was carried out on an Oxic Paleustalf soil in southern Nigeria. With application of N, P, and K fertilizer, there were no yield differences between crops grown with alley cropping compared to control plots. With no fertilizer application, alley-cropped paitsai [Brassica chinensis L.) enhanced yield and plant mineral concentration. Alley cropping gave higher plant stand o f direct-seeded paitsai, mainlydue to reduced soil erosion.